2012
DOI: 10.1128/aac.05654-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Characterization of an Acquired Subgroup B3 Metallo-β-Lactamase Gene, bla AIM-1 , and Its Unique Genetic Context in Pseudomonas aeruginosa from Australia

Abstract: e Three clinical Pseudomonas aeruginosa isolates (WCH2677, WCH2813, and WCH2837) isolated from the Women's and Children's Hospital, Adelaide, Australia, produced a metallo-␤-lactamase (MBL)-positive Etest result. All isolates were PCR negative for known MBL genes. A gene bank was created, and an MBL gene, designated bla AIM-1 , was cloned and fully characterized. The encoded enzyme, AIM-1, is a group B3 MBL that has the highest level of identity to THIN-B and L1. It is chromosomal and flanked by two copies (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 46 publications
3
78
0
4
Order By: Relevance
“…Based on multiple amino acid sequence alignment, PEDO-1, PEDO-2, CPS-1, and ESP-1 ␤-lactamases showed maximum identity (56 to 75%) to GOB-1 ␤-lactamase from Elizabethkingia meningoseptica (formerly Chryseobacterium meningosepticum) (34) (see Table S4 in the supplemental material). SPG-1 showed the highest amino acid identity (47%) to CAU-1 ␤-lactamase from Caulobacter crescentus (35), and MSI-1 ␤-lactamase displayed approximately 40% identity to SMB-1 and AIM-1 ␤-lactamases from Serratia marcescens (13) and Pseudomonas aeruginosa (36), respectively (see Table S4 in the supplemental material). MSI-1 (class B ␤-lactamase homologue) and MSI-OXA (class D ␤-lactamase homologue) displayed the highest amino acid identity (64 to 66%) to putative domains in Massilia timonae strain CCUG 45783, where the two domains were fused to form a putative bifunctional MBL-OXA enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Based on multiple amino acid sequence alignment, PEDO-1, PEDO-2, CPS-1, and ESP-1 ␤-lactamases showed maximum identity (56 to 75%) to GOB-1 ␤-lactamase from Elizabethkingia meningoseptica (formerly Chryseobacterium meningosepticum) (34) (see Table S4 in the supplemental material). SPG-1 showed the highest amino acid identity (47%) to CAU-1 ␤-lactamase from Caulobacter crescentus (35), and MSI-1 ␤-lactamase displayed approximately 40% identity to SMB-1 and AIM-1 ␤-lactamases from Serratia marcescens (13) and Pseudomonas aeruginosa (36), respectively (see Table S4 in the supplemental material). MSI-1 (class B ␤-lactamase homologue) and MSI-OXA (class D ␤-lactamase homologue) displayed the highest amino acid identity (64 to 66%) to putative domains in Massilia timonae strain CCUG 45783, where the two domains were fused to form a putative bifunctional MBL-OXA enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these findings suggested that, similar to other ␤-lactamases, including some acquired MBLs, namely, bla SPM-1 and bla AIM-1 (32,33), an ISCR element was involved in the capture and mobilization of bla FIM-1 and underscored the potential role of (27)(28)(29) or deduced using the SignalP software. The sequence sources were as follows: FIM-1 (the present study), NDM-1 (GenBank/EMBL accession no.…”
Section: Resultsmentioning
confidence: 89%
“…For example, Klebsiella pneumoniae carbapenemase (KPC) is the carbapenemase found most frequently in Enterobacteriaceae in the United States (1), while NDM is frequently found in the Indian subcontinent (2) and SPM is found in Brazil (3). Despite the fact that there have been reports of KPC (4), NDM (5,6), OXA-48 (7) and even a unique carbapenemase, AIM-1 (8), in Australia, none have become dominant there. In Australia, IMP-producing Enterobacteriaceae, particularly Enterobacter cloacae, have been reported to be the predominant form of CPE (9)(10)(11).…”
mentioning
confidence: 99%